2013
DOI: 10.1504/ijmne.2013.054483
|View full text |Cite
|
Sign up to set email alerts
|

The effects of total quality management on customer service management in the Nigerian banking industry: an empirical analysis

Abstract: This paper investigates the effectiveness of the critical success factors (CSFs) of total quality management (TQM) on customer service management (CSM) in the Nigerian banking industry. The empirical study was conducted via a survey on six, out of the 22 banks that have implemented TQM due to the 2004 consolidation exercise of the Central Bank of Nigeria (CBN). Using the Malcolm Baldrige National Quality Award (MBNQA) 2001 award framework, factors manifesting customer service management were regressed on the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The objective of the research reported in this paper was to operationalize a model of a successful BPR implementation, and to test the model, via modeling (using structural equation modeling-SEM) the CSFs of BPR on performance measures in the oil and gas industry. These objectives were achieved using the following procedures: factor analyses (exploratory factor analysis and confirmatory factor analysis) and Structural Equation Modelling (SEM) (Asikhia and Awolusi, 2015;Mustapha et al, 2014;Asika and Awolusi, 2013;Awolusi, 2013b;Awolusi, 2013c). Since the focus of this paper was the analysis of what was done after the development of the conceptual framework, consequently, additional analysis was conducted to determine the causal path analysis using the Pearson's product correlation coefficient (PPMC) and SEM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of the research reported in this paper was to operationalize a model of a successful BPR implementation, and to test the model, via modeling (using structural equation modeling-SEM) the CSFs of BPR on performance measures in the oil and gas industry. These objectives were achieved using the following procedures: factor analyses (exploratory factor analysis and confirmatory factor analysis) and Structural Equation Modelling (SEM) (Asikhia and Awolusi, 2015;Mustapha et al, 2014;Asika and Awolusi, 2013;Awolusi, 2013b;Awolusi, 2013c). Since the focus of this paper was the analysis of what was done after the development of the conceptual framework, consequently, additional analysis was conducted to determine the causal path analysis using the Pearson's product correlation coefficient (PPMC) and SEM.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, organizational performance, a secondary measure, was initially represented by financial measures such as profitability, growth, productivity; and non-financial variables such as customer services and sustainable competitive advantage. However, many studies have established the link between various performance indices and BPR efforts (Asika and Awolusi, 2013;Awolusi, 2013b;Awolusi, 2013c;Ascari et al, 1995;Smith, 2003). These studies were aimed at helping firms improve their competitiveness, by improving operations and processes.…”
Section: Critical Success Factors (Csfs) Of Bprmentioning
confidence: 99%
“…The resource-based theory views internal organizational factors as the determinants of FDI inflows (Steers & Nardon, 2006;Hill, 2013;Porter, 1990). The resource-based view suggests that valuable firm resources -comprising tangible and intangible elements -are usually scarce, imperfectly imitable, and lacking in direct substitutes (Asikhia and Awolusi, 2015;Awolusi, 2013b;Brouthers & Hennart, 2007). It is about producing the most value from one's existing capabilities and resources by combining these with others' sources of advantage, and, in this, ensuring that complementarity is paramount (Hill, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Subari (2014b, 2014a) were find the coexistence of critical factors of ISO 9000, soft and hard dimensions of TQM in Malaysian industries by depicting six TQM models to establish a better environment. Awolusi (2013) had proposed the conceptual model to investigate the effectiveness of the critical success factors of TQM in the Nigerian banking industry. Ali and Alolayyan (2013) had investigated the performance of TQM practices in Jordanian hospitals, especially in the dimension of patient result and staff/work system results.…”
Section: Literature Reviewmentioning
confidence: 99%